Il diritto al risarcimento educativo dei detenuti - Torlone, Francesca (Studies on Adult Learning and Education, 2016)
The enforcement of the sentence in a (re)educational perspective is a highly debated topic in different approaches, including the multidisciplinary ones. In this volume, the topic is discussed from a compensatory perspective, namely through the acknowledgement of the need to prepare educational tools to contrast the 'adverse educational actions', to which the prison population may be exposed, and to the phenomenon of repeated infractions. In addition to the elements of the treatment program (which is structured, intentional, legally regulated and procedure-like), every phase of the sentence enforcement, even those taken for granted, includes an educational value and presents itself as a growth and improvement opportunity for each prisoner. As evidence to the variety of experiences (in the educational sense), this volume collects a series of contributions by professionals from the criminal justice system who support the changing processes of prisoners.